2019
DOI: 10.3390/joitmc5010006
|View full text |Cite
|
Sign up to set email alerts
|

Open Principles in New Business Models for Information Systems

Abstract: Open source software and open innovation are an important resource for today’s industries. Communities collaboratively create different kind of publicly available value, boosting innovation and also technology. However, whereas this value is generated and captured by various involved parties, the outcomes are, in many cases, commercialized by companies who build their business models on this openness. Thus, current business model representations used for these open systems mainly focus on the commercial side o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Though until around 2000-2001, a business model was defined as a kind of description or statement, it has since been accepted as a kind of concept model or architecture [9,11,13]. Recent business model studies, such as business model prism for arts and cultural organizations, open principles in new business models, dynamics in business model frameworks, and a new and emerging business model of artificial intelligence including relevant platforms, are almost all focused on concept model or architecture [14][15][16]. The common definition of a business model from the concept model or architecture perspective is "the concept model or architecture which provides value proposition, and revenue creation" [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though until around 2000-2001, a business model was defined as a kind of description or statement, it has since been accepted as a kind of concept model or architecture [9,11,13]. Recent business model studies, such as business model prism for arts and cultural organizations, open principles in new business models, dynamics in business model frameworks, and a new and emerging business model of artificial intelligence including relevant platforms, are almost all focused on concept model or architecture [14][15][16]. The common definition of a business model from the concept model or architecture perspective is "the concept model or architecture which provides value proposition, and revenue creation" [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Amazon expanded its online discounting E-commerce model to a broad range of products and services. Environmental scarcity during an economic downturn challenged Amazon's basic model, in addition to inducing organizational members' creativity to engage in open innovation considering their business models [72]. Thus, open environmental constraints during an economic recession often encourage firms to take significant risks that inspire innovation [73].…”
Section: Recession and Innovationmentioning
confidence: 99%
“…Open innovation micro-dynamics. Source: [1].Open principles in new business models of information systems, learning patterns in dynamic technological system lifecycles, triggers of collaborative innovation in online user communities, and the transformation from design thinking to artistic thinking are also emerging themes of open innovation micro-dynamics[64][65][66][67].In uncertain markets, new metrics can help companies to play poker as well as chess by managing open innovation[68]. Specifically, databases, case studies, and theoretical research have revealed that SMEs require motivations of open innovation with good control of the increasing complexity from various aspects[17,23,69,70].…”
mentioning
confidence: 99%